How can digital economy development empower high-quality economic development? - Chen, Wen; Du, Xiaoyu; Lan, Wei; Wu, Weili; Zhao, Murong (Technological and Economic Development of Economy, 2023)
The role of the digital economy in economic transformation is increasingly prominent. This paper empirically examines how the digital economy affects TFP and its mechanism using Chinese provincial panel data. The results show that the impact of the digital economy on regional TFP is U-shaped. Further studies show that digital economy development may improve regional TFP through two channels: stimulating innovation and promoting entrepreneurship. In addition, we also discuss the role of active government, effective market, and high-level judicial protection in digital economic policies improving economic growth. Based on our research results, we put forward some policy recommendations.First published online 17 April 2023